Transcranial Parenchymal Sonographic Findings in Patients With Cerebral Small Vessel Disease: A Preliminary Study. (11th September 2015) - Pavlović, Aleksandra M.; Pekmezović, Tatjana; Jovanović, Zagorka; Medjedović, Tamara Svabic; Veselinović, Nikola; Norton, Melanie C.; Sternić, Nada
Abstract : Objectives: Patients with cerebral small vessel disease often present with various motor, cognitive, and emotional changes, including gait disturbances, parkinsonism, and depression. Substantia nigra hyperechogenicity, brain stem raphe hypoechogenicity, ventricle diameters, and sonographic characteristics of other brain structures on transcranial sonography have been increasingly used as biomarkers in a range of neurologic diseases. We aimed to explore the frequency and clinical correlates of transcranial sonographic findings in symptomatic patients with small vessel disease. Methods: In a cross‐sectional study, neurologic, cognitive, and emotional statuses and transcranial sonographic and magnetic resonance imaging findings were compared between 102 patients with small vessel disease and 45 healthy age‐ and sex‐matched control participants. Results: Compared to healthy controls, small vessel disease cases had more frequent brain stem raphe hypoechogenicity (55.9% versus 11.1%; P < .0001), substantia nigra hyperechogenicity (30.4% versus 11.1%; P = .022), and enlarged third ventricles ( P < .0001). Substantia nigra hyperechogenicity correlated with gait disturbances, extrapyramidal features, and cognitive impairment. Brain stem raphe hypoechogenicity was associated with the diagnosis of depression. Enlargement of the third and lateral ventricles was more frequent in patients with cognitive impairment. Pathologic substantia nigra hyperechogenicity and enlarged ventricles were associated with the severity of cerebral ischemic lesions. Conclusions: Transcranial sonography shows pathologic findings in a substantial number of patients with small vessel disease, probably reflecting disruption of frontostriatal pathways.